PENGARUH DIVERSIFIKASI GEOGRAFIS, DIVERSIFIKASI INDUSTRI, KONSENTRASI KEPEMILIKAN PERUSAHAAN, DAN MASA PERIKATAN AUDIT TERHADAP MANAJEMEN LABA - Dewi Fatmawati; Arifin Sabeni (Diponegoro Journal of Accounting, 2013)
This study aims to examine and analyze the influence of geographic diversification, industrial diversification, firm ownership concentration, and audit tenure to earnings management in manufacturing companies. Discretionary accrual used as proxy for earnings management is counted by modified  Jones model. Geographic and industrial diversification are measured by the number of firms’ geographic and industrial segments. Firm ownership concentration is measured by percentage of the shares ownership owned by the largest shareholder. Audit tenure is measured by amount of  year of work relation between auditee and the last public accountant firm.This study is undertaken using documentary method and using data from annual reports, financial statements, and IDX. It uses multiple regression technique as method of analysis. There are 95 manufacturing companies listed on IDX in 2011 used as sample.The result of this study indicates that both geographic diversification and audit tenure have positive significant influence to earnings management. The more a company has geographic segments, the higher the company performs earnings management. The longer the audit tenure, the higher the company undertake earnings management as well. Whereas both industrial diversification and firm ownership concentration don’t have significant influence to earnings management.